Optimización para motores de búsqueda en contenidos periodísticos digitales del Ecuador - Avilés Pisco, Mileysha Marisol (2021)
At present, the world is immersed in constant changes due to technological advances, which have generated advantages in different fields of study and journalism is not far behind. By virtue of the consumption of news by Internet users, cybermedia to attract new readers have sought mechanisms in order to obtain web positioning in search engines through journalistic newsrooms. Given this fact, the objective of this case study is to know how the Search Engine Optimization (SEO) tool allows achieving the visibility and positioning necessary for a news item on a media website to remain in the first place search page. For this, an observation is made by comparing journalistic content in different cybermedia in Ecuador to know the use of the SEO that it develops.